A bidirectional relationship between cognitive reserve and cognition among older adults in a rural Chinese community: a cross-lagged design - Chen, Hao; Jiang, Zhiyue; Hu, Jin; Yang, Xing; Gui, Shiqi; Li, Qiushuo; Wang, Jing; Yang, Jingyuan (Frontiers in Psychology, 2023)
Background The concept of cognitive reserve (CR) plays a crucial role in understanding cognitive aging and resilience. Accumulating evidence revealed the influence of CR proxy on cognitive function, but it remains unknown whether a reverse association or reciprocal effect exists. Objective The aim of this study is to observe the bidirectional relationship between cognitive reserve proxies and cognitive function among older adults in rural Chinese communities, providing a better understanding of the underlying mechanisms and potential moderating factors involved. Method This longitudinal study analyzed 792 older adults (70.23 ± 5.87 years; 59.8%female) aged 60 years and older from the health status of rural older adults (HSRO) study over a 3-year period. Cognition was assessed by the Mini-Mental State Examination (MMSE). Cross-lagged panel modeling was utilized to analyze the interrelationship between cognitive reserve proxies and cognitive performance. Additionally, latent profile analysis was employed to identify different subtypes of neuropathic load within the study population. Results Our cross-lagged analyses revealed significant associations between CR at T0 and MMSE scores at T1 (β = 0.81), as well as between MMSE scores at T0 and CR at T1 (β = 0.04). However, when conducting stratified analyses, we found no significant lagged relationships among individuals with high neuropathic load or those at an advanced age (p > 0.05). Furthermore, our longitudinal comparisons indicated changes in the contribution of CR proxy factors over time. Conclusion The findings suggested a bidirectional relationship between cognitive reserve and cognitive performance in older adults. These results emphasized the importance of implementing timely public health measures to enhance cognitive reserve and cognitive performance ultimately promoting healthier aging among older adults.